2012
DOI: 10.1177/1040638712466554
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective swine influenza serological surveillance in the four highest pig density provinces of Thailand before the introduction of the 2009 pandemic Influenza A virus subtype H1N1 using various antibody detection assays

Abstract: Genetic characterization of the hemagglutinin gene of the 6 selected Thai Swine influenza virus (SIV) isolates (4 H1 and 2 H3 isolates) used in the establishment of a hemagglutination inhibition (HI) assay was analyzed. Based on the phylogenetic analysis, Thai SIVs could be divided into 3 clusters of the H1 viruses (clusters I and II belonging to classical swine H1α, and cluster III belonging to classical swine H1γ), and 2 clusters of the H3 viruses both belonging to human-like 1970s. The serological results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 41 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…The use of a large panel of antigens for HI assays is recommended to correctly identify the dominant strains in the country and also to rapidly detect any unusual subtypes of influenza A viruses in pig populations. Furthermore, antigens for HI tests should be regularly compared with those from circulating strains in a given country or region (Sreta et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The use of a large panel of antigens for HI assays is recommended to correctly identify the dominant strains in the country and also to rapidly detect any unusual subtypes of influenza A viruses in pig populations. Furthermore, antigens for HI tests should be regularly compared with those from circulating strains in a given country or region (Sreta et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…It is noted that pig had antibody against pdmH1N1, even though the pdmH1N1 viruses www.nature.com/scientificreports/ could not be identified in the pig farm. It has been reported that no cross-reaction between antibodies against H1-S-IAV and H1 pandemic viruses 30 . Thus, the HI titer result confirmed that pigs in this farm were exposed to both endemic S-IAV-H1 and S-IAV-H3 and pdmH1N1.…”
Section: Discussionmentioning
confidence: 99%
“…Real-time RT-PCR (RT-qPCR) has provided ample applications for rapid and sensitive molecular virological diagnosis [14]. Serology in swine influenza has been found useful for retrospective epidemiological investigations e.g., [15], estimation of disease incidence e.g., [16], and control of vaccination success e.g., [17]. Several commercial ELISAs for detection of generic IAV nucleocapsid protein (NP)-specific antibodies in pigs are available and recommended for use e.g., [18].…”
Section: Introductionmentioning
confidence: 99%